Challenges of Digital Technology in Promoting Digital Learning at SMP Islam Terpadu An-Nur - Tri Muthoharoh; Murhartoyo Murhartoyo; Aslamiah Aslamiah; Celia Cinantya (CV. Global Cendekia Inti, 2026)
This study examines the challenges of digital technology in promoting digital learning at An-Nur Integrated Islamic Junior High School amidst the era of disruption and the Industrial Revolution 4.0. The urgency of this research lies in the vital need for educational institutions to adapt and equip students with 21st-century skills through technology integration. The goal is to build a holistic and sustainable digital learning ecosystem. The study employed a qualitative approach with a comprehensive strategy, emphasizing teacher capacity building as a key pillar. This was achieved through regular training and the use of artificial intelligence (AI), supported by adaptive leadership. Data collection techniques included observation, in-depth interviews, and documentation. Findings indicate that although the school has provided modern hardware and software, significant challenges arise related to infrastructure, particularly internet access and stability, due to limited service providers. The school responded by considering proactive solutions such as satellite internet and community education, as well as implementing adaptive budget allocations for teacher training and educational technology. An integrated monitoring and evaluation system, including regular teacher meetings that facilitate discussion and collaborative problem-solving, ensures the initiative runs optimally. In conclusion, SMP IT An-Nur has demonstrated significant progress in fostering a culture of innovation and experimentation through budget flexibility, KPI-based human resource development, and transformational leadership to address digital challenges.